Development of HOTS Assessment Tools to Measure Achievement in Acid-Base Learning Outcomes - Rauzatul Jannah; Isna Rezkia Lukman; Fiqih Choiruddin; Naila Nurul Izzah; Ulfa Zahra; Halimatus Sakdiah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to develop a valid and reliable assessment instrument to measure students' higher-order thinking skills in the context of acid-base chemistry. The research employed a Research and Development (RD) approach using the 4-D model, which includes the stages of Define, Design, Develop, and Disseminate. The initial product was validated through expert judgment, evaluated for feasibility by chemistry teachers, and subjected to field testing. The study involved 200 twelfth-grade science students from SMAN Bireuen. Data collection techniques included interviews, questionnaires, and tests. Data collection instruments included interview guidelines, item validation sheets, feasibility evaluation forms, and multiple-choice questions with open-ended justifications. The research findings revealed that the material validation assessment obtained an average score of 47.5 ( 46.194), categorized as "very good." Similarly, the feasibility assessment achieved an average score of 72.5 ( 67.188), also falling within the "very good" category. A total of 30 test items from the trial were analyzed in terms of validity, reliability, difficulty level, discrimination index, and distractor effectiveness. Therefore, it can be concluded that the assessment instrument is appropriate for measuring higher-order thinking skills in the topic of acid-base chemistry.